Transvaginal Natural Orifice Transluminal Endoscopic Surgery for Surgical Staging of Early-Stage Ovarian Cancers: A Report of Two Cases - Hurni, Yannick; Romito, Fabien; Huber, Daniela (Frontiers in Surgery, 2022)
Surgical staging is essential in the management of ovarian cancers. This staging has traditionally been performed by laparotomy, but minimally invasive techniques are increasingly employed. Transvaginal natural orifice transluminal endoscopic surgery (vNOTES) is a promising technique in the field of gynecological oncology. We report 2 cases of vNOTES surgical staging for suspicious ovarian tumors. We operated on 2 patients aged of 81 and 62 years for low-grade serous ovarian carcinoma and ovarian cystadenofibroma, respectively. We performed surgical staging with a pure vNOTES technique for the first patient and used a hybrid approach for the second. No intraoperative or postoperative complications were observed. We suggest that vNOTES is a feasible and effective approach to surgically manage early-stage ovarian cancers.